Dalargin antistress effects in experimental chronic stress model - Kirchev, V. (Journal of Education, Health and Sport, 2024)
The problem of acute and chronic stress and the associated majority organisms’ physiological systems functional disorders has recently attracted the attention of both practical and general theoretical specialists. Stress and its consequences are the largest cause of morbidity and mortality in developed countries. We supposed it should be important to study the antistress efficacy of one of the regulatory peptides - dalargin - in rats on conditions of chronic stress. The purpose of the work was to investigate the stress protective effects of peptide compound dalargin in conditions of experimental chronic stress model. In rats under conditions of chronic stress, the severity of aggressive-defensive behavior was determined, morphometric studies were performed, and the effect of dalargin on these indicators was studied. The data obtained showed the increase of aggressive-defensive behaviour severity in rats under chronic stress. The weight of both stress-competent and lymphopoietic organs continue to increased in rats with chronic stress experimental conditions which is accompanied by adrenal glands both cortical and medulla layers width increase. The use of dalargin in rats with chronic stress contributed to above mentioned behavioural and morphological changes normalization. Author suppose that dalargin stress-protective effects in rats in conditions of chronic stress model are the experimental background for this compound antistress efficacy testing reasonability for human body stress-induced changes complex pharmacological correction performing.